Financial Literacy Assistance and Prevention of Fintech Lending Dependency for Employees of PT. Yushin: Pendampingan Literasi Keuangan dan Pencegahan Ketergantungan Fintech Lending bagi Karyawan PT. Yushin - Yulijantik, Yulijantik; Sufatmi, Sufatmi; Mujanah, Siti; Ridwan, M. Sihab (Institut Riset dan Publikasi Indonesia, 2026)
Employees of PT. Yushin, a manufacturing company in East Java, face serious problems related to consumptive behavior and dependence on fintech lending services that negatively impact their performance and financial well-being. Preliminary studies showed a 12% increase in absenteeism and a decline in average performance scores from 78.4 to 72.1 (scale of 100) during 2022–2023. This community service activity aims to improve employees’ financial literacy, raise awareness of the risks of fintech lending dependency, and encourage healthier financial behavior. Implementation methods included three phases: (1) preparation through needs surveys, module development, and evaluation instruments; (2) a full-day financial literacy workshop with four content sessions; and (3) evaluation through pre-test and post-test assessments. The activity involved 80 permanent employees selected purposively. Results showed an average increase in financial literacy scores of 34.2%, from 57.8 to 77.6 (scale of 100). The highest improvement was in understanding fintech lending risks (47.3%) and personal financial management (38.6%). A total of 93.8% of participants expressed satisfaction and readiness to apply healthy financial principles. This activity produced tangible outcomes including improved financial literacy and management’s commitment to follow up with a sustainable Employee Financial Wellness program